2015
DOI: 10.3390/ijms160817857
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Mutual Inhibition of ERK and mTOR in PLCγ1-Mediated MMP-13 Expression in Human Osteoarthritis Chondrocytes

Abstract: The issue of whether ERK activation determines matrix synthesis or degradation in osteoarthritis (OA) pathogenesis currently remains controversial. Our previous study shows that PLCγ1 and mTOR are involved in the matrix metabolism of OA cartilage. Investigating the interplays of PLCγ1, mTOR and ERK in matrix degradation of OA will facilitate future attempts to manipulate ERK in OA prevention and therapy. Here, cultured human normal chondrocytes and OA chondrocytes were treated with different inhibitors or tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…Activated ERK could regulate autophagy either positively or negatively [24][25][26]. Meanwhile, PLCγ1 regulation of ERK phosphorylation has been demonstrated previously [27,28]. Our results that overexpression of PLCγ1 elevated ERK level concomitant with a decrease in LC3B-II and an increase in P62 exhibited the negative regulation of PLCγ1/ERK axis on autophagy in human lung adenocarcinoma A549 cells, thereby suggesting that the inhibition of PLCγ1/ERK axis contributed to autophagy induction in human lung adenocarcinoma A549 cells (Fig.8).…”
Section: Discussionsupporting
confidence: 74%
“…Activated ERK could regulate autophagy either positively or negatively [24][25][26]. Meanwhile, PLCγ1 regulation of ERK phosphorylation has been demonstrated previously [27,28]. Our results that overexpression of PLCγ1 elevated ERK level concomitant with a decrease in LC3B-II and an increase in P62 exhibited the negative regulation of PLCγ1/ERK axis on autophagy in human lung adenocarcinoma A549 cells, thereby suggesting that the inhibition of PLCγ1/ERK axis contributed to autophagy induction in human lung adenocarcinoma A549 cells (Fig.8).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, inhibition of the p38-MARK signaling pathway suppressed apoptosis and expression of pro-inflammatory cytokines of IL-1,IL-6 and TNF-α in osteoarthritis chondrocytes [39]. Besides, the inhibition of ERK was involved in PLCγ1-mediated MMP-13 expression in human OA chondrocytes, with important implication for the understanding of OA pathogenesis [40]. In our study, we explored that CXCR4 silencing blocked LPS-activated NF-κB and MAPK/ERK pathways in ATGC5 cells, further regulating cell viability, apoptosis and inflammatory injury in OA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of PLCγ1 in OA remains clear. Our recent observation also showed that PLCγ1 was expressed at elevated level in human OA chondrocytes than in normal chondrocytes, serving as a pivotal element of signal cascades constituted by ERK and mTOR to promote matrix degradation in human OA chondrocytes [ 13 , 14 ]. We then hypothesized that PLCγ1 could be involved in OA chondrocyte metabolism, contributing to matrix degradation.…”
Section: Introductionmentioning
confidence: 99%